Hydrogen and methane emissions from beef cattle and their rumen microbial community vary with diet, time after feeding and genotype. Issue 3 (14th August 2014) - Rooke, John A.; Wallace, R. John; Duthie, Carol-Anne; McKain, Nest; de Souza, Shirley Motta; Hyslop, Jimmy J.; Ross, David W.; Waterhouse, Tony; Roehe, Rainer
<x content-type="archive" xml:space="preserve">Abstract</x> The aims of the present study were to quantify hydrogen (H2) and methane (CH4) emissions from beef cattle under different dietary conditions and to assess how cattle genotype and rumen microbial community affected these emissions. A total of thirty-six Aberdeen Angus-sired (AAx) and thirty-six Limousin-sired (LIMx) steers were fed two diets with forage:concentrate ratios (DM basis) of either 8:92 (concentrate) or 52:48 (mixed). Each diet was fed to eighteen animals of each genotype. Methane (CH4) and H2 emissions were measured individually in indirect respiration chambers. H2 emissions (mmol/min) varied greatly throughout the day, being highest after feed consumption, and averaged about 0·10 mol H2/mol CH4. Higher H2 emissions (mol/kg DM intake) were recorded in steers fed the mixed diet. Higher CH4 emissions (mol/d and mol/kg DM intake) were recorded in steers fed the mixed diet (P< 0·001); the AAx steers produced more CH4 on a daily basis (mol/d, P< 0·05) but not on a DM intake basis (mol/kg DM intake). Archaea (P= 0·002) and protozoa (P< 0·001) were found to be more abundant and total bacteria (P< 0·001) less abundant (P< 0·001) on feeding the mixed diet. The relative abundance of Clostridium cluster IV was found to be greater (P< 0·001) and that of cluster XIVa (P= 0·025) lower on feeding the mixed diet. The relative abundance of Bacteroides plus Prevotella was greater (P= 0·018) and that of Clostridium cluster IV lower (P= 0·031) in the LIMx steers. There were no significant relationships between H2 emissions and microbial abundance. In conclusion, the rate of H2 production immediately after feeding may lead to transient overloading of methanogenic archaea capacity to use H2, resulting in peaks in H2 emissions from beef cattle.